(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the scientific and methodological foundations of the formation of business skills in students within the framework of the primary education system. Through the introduction of innovative methods and integrated approaches to the educational process, ways of developing important qualities such as economic thinking, initiative and responsibility are revealed in students.